2007
DOI: 10.1523/jneurosci.0564-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Neural Substrates of Goal-Directed Learning in the Human Brain

Abstract: Instrumental conditioning is considered to involve at least two distinct learning systems: a goal-directed system that learns associations between responses and the incentive value of outcomes, and a habit system that learns associations between stimuli and responses without any link to the outcome that that response engendered. Lesion studies in rodents suggest that these two distinct components of instrumental conditioning may be mediated by anatomically distinct neural systems. The aim of the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
440
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(490 citation statements)
references
References 48 publications
46
440
1
Order By: Relevance
“…Similar findings hold in closely related paradigms in humans (Valentin et al, 2007;de Wit et al, 2009;Tricomi et al, 2009;Daw et al, 2011). The shift from early devaluation sensitivity to later devaluation insensitivity can be explained by the statistical properties of model-based and model-free systems, respectively.…”
Section: Motivational Shiftssupporting
confidence: 74%
See 1 more Smart Citation
“…Similar findings hold in closely related paradigms in humans (Valentin et al, 2007;de Wit et al, 2009;Tricomi et al, 2009;Daw et al, 2011). The shift from early devaluation sensitivity to later devaluation insensitivity can be explained by the statistical properties of model-based and model-free systems, respectively.…”
Section: Motivational Shiftssupporting
confidence: 74%
“…In other words, the information reflected in the habitual behaviour is present in a stimulus-action value Q MF (s, a), which captures how valuable an action is in a particular state, but without providing any information about the actual outcomes. An insensitivity to motivational changes is characteristic of cached values and habitual choices (McClure et al, 2003b;Daw et al, 2005;Valentin et al, 2007;Daw et al, 2011;Wunderlich et al, 2012a). Thus, instrumental learning derived from the accumulation of dopaminergic prediction errors accounts for outcome-insensitive habits.…”
Section: Motivational Shiftsmentioning
confidence: 99%
“…In the addict, the value that is attributed to certain events or cues seems to be altered (Garavan et al, 2000;Ahmed et al, 2002;Grigson and Twining, 2002). There is substantial evidence that the OFC mediates subjective value attribution and is an integral part in adaptive decision making (Tremblay and Schultz, 1999;Knutson et al, 2000;Breiter et al, 2001;Elliott et al, 2003;Valentin et al, 2007). Indeed, a recent activation study in cocaine users confirmed the involvement of the lateral OFC in deficient attribution of feedback values (Goldstein et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the more they judged the chocolate odor as pleasant (r = .64, p < .001,), the more they preferred the CS+ compared with the CSÀ and the baseline. (2008): We selected three geometric complex figures typically used in human conditioning paradigms (Gottfried et al, 2003;O'Doherty et al, 2004;Valentin, Dickinson, & O'Doherty, 2007) that in a pilot study (n = 26) were rated as equally neutral on a pleasantness scale. During ''task-on'' periods, the CS+ or CSÀ was displayed, a target appeared at the center of the image, and participants had to press a keyboard that triggers odor release.…”
Section: Pavlovian Conditioningmentioning
confidence: 99%